Marketing Strategy Analysis of Culinary Tourism Products in Suranadi Village, Narmada District, West Lombok Regency - I Made Subrata; Sulaeman Sulaeman; Tama Krisnahadi (Business Management, 2026)
This study aims to identify various alternative marketing strategies for culinary tourism products in Suranadi Village. The benefit of this research is to provide input for MSME actors who produce and sell culinary tourism products in Suranadi Village, Narmada District, in marketing their products so that they can obtain higher income.  The type of research used is descriptive research, with data collection methods employing the case study method, and data analysis using SWOT analysis. The results of this study are as follows: 1)Promoting culinary tourism products through social media or digital promotion, 2) Establishing cooperative relationships with various parties, especially those related to culinary tourism and natural tourism dan 3)Inviting investors who are willing to participate in tourism development, particularly in culinary tourism products.